Choice of primary healthcare providers among population in urban areas of low- and middle-income countries—a protocol for systematic review of literature - Md. Zahid Hasan; Edward J D Webb; Zahidul Quayyum; Tim Ensor (Systematic Reviews)
Abstract Introduction Strengthening and reforming the urban primary healthcare (PHC) system is essential to efficiently deliver need-based healthcare services to the rapidly increasing urban poor population. Such reforms of PHC system need to emphasize the opinion of patients in co-designing services in order that delivery of services can be accessed effectively by the urban population in a timely and low-cost way. Hence, it is important to identify the preference of urban population while choosing healthcare providers. The aim of this proposed protocol is to summarize a planned systematic review of existing evidence on the attributes considered for choosing PHC providers in urban settings of low- and middle-income countries (LMICs), as classified by the World Bank. Methods and analyses An inclusive literature search will be conducted in electronic databases including Pubmed/MEDLINE, Embase, Global Health, Cochrane Library, Web of Science, and Scopus. Databases will be searched from the earliest date of entry until March 30, 2024. Database search will be supplemented by manual search of citations, reference lists, and grey literature sources. Following the pre-set inclusion and exclusion criterion, two researchers will independently screen all the retrieved studies in Covidence. Any discrepancies will be resolved through a discussion between two researchers, and if disagreements persist, a third reviewer will be consulted. The methodological quality of included studies will be appraised using checklist for Conjoint Analysis studies and the Mixed Methods Appraisal Tool (MMAT). An Excel-based data extraction table will be developed, piloted, and refined during the review process. Preference attributes will be identified and analyzed according to their types. The systematic review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta‑Analyses (PRISMA) guidelines. Discussion The identification of attributes, their influence on preference, and heterogeneity with socioeconomic characteristics of the population will help the policymakers and researchers to design targeted PHC interventions. Such evidence will be also useful to design choice experiment studies to quantify the preferred attributes of PHC providers in urban context of LMICs. Systematic review registration PROSPERO CRD42023409720.